Food security & sustainability: Malaysian context - Zahari, Rustam Khairi; Younus, Mohammed Amer (2012)
Amongst the encounters facing the world today, the urgency of providing food security to the growing human population and slowing the rapid loss of irreplaceable biological diversity appear large. The concept of food security has been undergoing an evolutionary change during the last 50 years. In the nineteen fifties, food security was considered essentially in terms of production. It was assumed that adequate production will assure adequate availability of food in the market as well as in the household. In the seventies, it became clear that availability alone does not lead to food security, since those who lack purchasing power will not be able to have access to balanced diets [1]. More recently, it is becoming obvious that even if availability and access are satisfactory, the biological absorption of food in the body is related to the consumption of clean drinking water as well as to environmental hygiene, primary health care and primary education. Finally, even if physical and economic access to food is assured, ecological factors will determine the long-term sustainability of food security systems.